Factors associated with the discontinuation of dipeptidyl peptidase-4 inhibitors (DPP-4is) after initiation of insulin. (3rd March 2020) - Fernandes, Gail; Matos, Joana E.; Jaffe, Dena H.; Beyer, Grace; Yang, Lingfeng; Iglay, Kristy; Gantz, Ira; Rajpathak, Swapnil
Abstract: Objective: Type 2 diabetes (T2D) is a prevalent health problem. Oral agents, with the exception of metformin, are often discontinued with the initiation of insulin. The objective was to understand the proportion of patients discontinuing dipeptidyl peptidase-4 inhibitors (DPP-4is) and the reasons for the decision to discontinue. Methods: A retrospective study using a health claims database investigated discontinuation of DPP-4i in adult patients on a dual therapy of metformin and DPP-4i who initiated insulin ( n = 3391). An online survey administered to 406 physicians in the US examined reasons for discontinuation. Physicians surveyed included endocrinologists (34.5%), general practitioners (32.5%), internal medicine specialists (30.5%), and diabetologists (2.5%), treating a monthly average of 154 patients. Results: Among patients treated with metformin and DPP-4is who were newly prescribed insulin, 33.3 and 57.3% discontinued DPP-4i therapy within 3 and 12 months, respectively. Patients who discontinued DPP-4i therapy had higher out-of-pocket costs and a greater proportion of renal and liver disease. Top 3 responses for discontinuation included adverse events/tolerability issues (58.9%), lack of efficacy/treatment goals not being met (55.4%) and additional cost of DPP-4i with insulin (48.5%). Top 3 responses for continuing DPP-4i included meeting treatment goals (70.7%), using a lower dose of insulin (65.3%) and good tolerability (48.0%). Physician characteristics, such as physician specialty, age, gender and location impacted to some extent the reasons for treatment decisions. Conclusions: A large proportion of patients discontinue DPP-4is in the real world when initiating insulin. The impact of physician characteristics in treatment decisions highlights the need for enhanced physician training and support as new clinical data emerges and therapy options are available.